PERAN MANAJEMEN PENDIDIKAN DALAM MENCIPTAKAN LINGKUNGAN BELAJAR KONDUSIF BAGI ANAK USIA DINI DI RA AHSANU AMALA NYAMPLUNGSARI - Hikma Fitriani; Mutammam Mutammam (STKIP Pesisir Selatan, 2026)
This research seeks to examine how educational management contributes to establishing a conducive learning atmosphere for children at RA Ahsanu Amala Nyamplungsari. A qualitative descriptive design was employed, with data gathered through interview with the school principal and document analysis. The collected information was analyzed using the Miles and Huberman framework, consisting of data redaction, data display, and conclusion formulation. The results reveal that the core management functions-planning, organizing, implementation, and evaluation-have been effectively carried out to foster a positive learning environment. Planning involves grouping students based on age and developmental level. Organization involves assigning tasks to teachers and class arrangements. Learning is implemented using the Independent Curriculum (Kurikulum Merdeka), incorporating icebreaking activities, teaching religious values, and providing motivation to students. Evaluations are conducted regularly to monitor student progress and improve the learning process. Thus, the implementation of educational management plays a significant role in helping create a safe, comfortable, and developmentally appropriate learning environment for early childhood.